2020
DOI: 10.1177/2040622320961599
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-glucose cotransporter 2 inhibitors and fracture risk in patients with type 2 diabetes mellitus: a meta-analysis of randomized controlled trials

Abstract: Background: Patients with type 2 diabetes mellitus (T2DM) have an increased risk of fracture compared with those without T2DM. Some oral glucose-lowering agents may increase the incidence of fracture. Whether sodium-glucose co-transporter 2 inhibitors (SGLT2is) are associated with increased risk of fracture remains unclear. Methods: We retrieved articles from PubMed, Embase, Cochrane Library database, and other sources up to 24 October 2019. We included randomized controlled trials (RCTs) that reported fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
0
11
1
Order By: Relevance
“…47 This increased fracture risk was not observed in the following Canagliflozin and Renal Outcomes in Type 2 Diabetes and Nephropathy trial and other large RCTs, 2,[4][5][6]17 nor was an association observed in subsequent meta-analyses. 48,49 A disproportionality and Bayesian analysis of Food and Drug Administration safety reporting data from 2004 to 2019 also showed no difference in fracture event reports for patients taking SGLT-2i vs SGLT-2i plus other diabetes agents. 50 Thus, cohort studies to assess the effect of SGLT-2i on fracture in routine practice are warranted.…”
Section: Discussionmentioning
confidence: 97%
“…47 This increased fracture risk was not observed in the following Canagliflozin and Renal Outcomes in Type 2 Diabetes and Nephropathy trial and other large RCTs, 2,[4][5][6]17 nor was an association observed in subsequent meta-analyses. 48,49 A disproportionality and Bayesian analysis of Food and Drug Administration safety reporting data from 2004 to 2019 also showed no difference in fracture event reports for patients taking SGLT-2i vs SGLT-2i plus other diabetes agents. 50 Thus, cohort studies to assess the effect of SGLT-2i on fracture in routine practice are warranted.…”
Section: Discussionmentioning
confidence: 97%
“…A systematic review suggested that canagliflozin is linked to an increased fracture rate ( 33 ), a conclusion that is similar with our results. One study suggested that SGLT2 inhibitors have neutral effects on fracture risk ( 34 ). In a clinical trial, SGLT2 inhibitors exhibited better benefits than other anti-diabetic drugs in T2DM patients suffering from chronic kidney disease ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis suggested only canagliflozin but none of the other SGLT2 inhibitors to increase fracture risk ( Lou et al, 2020 ) – suggesting compound specific differences.…”
Section: Discussionmentioning
confidence: 99%